1985
DOI: 10.1021/jo00221a034
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular olefinic aldehyde Prins reactions for the construction of five-membered rings

Abstract: At 100 °C (Reflux Temperature). A solution of 104 mg (0.414 mmol) of 34 dissolved in 7 mL of 95% formic acid was heated at reflux under nitrogen for 12 h. The formic acid was removed with a rotary evaporator, and the residue was diluted with 50 mL of 10% aqueous NaHCOs. The aqueous solution was extracted with 100 mL of CH2C12, and the organic phase was washed with brine, dried over Na2S04, and concentrated to give 112 mg of a yellow oil. The crude product was purified by flash chromatography on 5 g of silica u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…140 However, aldehyde 224 affords ene adduct 225 in 68% yield with 1 equivalent of Me 2 AlCl at À 72 1C, but not with SnCl 4 . 140 Sarkar reported that the ene reactions of 220 and 222 catalyzed by 5 mol% Sm(III) generated in situ from SmI 2 in CH 2 Cl 2 gives the trans cyclopentanols 226 and 227, respectively rather than the cis cyclopentanols 223 and 225 obtained with Me 2 AlCl or SnCl 4 . 141 This Sm(III) catalyst converts citronellal into a mixture of isopulegol (162a) in 15% yield and neoisopulegol (162b) in 45% yield indicating that it behaves as large catalyst that favors the boat transition state leading to 162b as discussed above (see Scheme 22).…”
Section: Scheme 24mentioning
confidence: 99%
See 2 more Smart Citations
“…140 However, aldehyde 224 affords ene adduct 225 in 68% yield with 1 equivalent of Me 2 AlCl at À 72 1C, but not with SnCl 4 . 140 Sarkar reported that the ene reactions of 220 and 222 catalyzed by 5 mol% Sm(III) generated in situ from SmI 2 in CH 2 Cl 2 gives the trans cyclopentanols 226 and 227, respectively rather than the cis cyclopentanols 223 and 225 obtained with Me 2 AlCl or SnCl 4 . 141 This Sm(III) catalyst converts citronellal into a mixture of isopulegol (162a) in 15% yield and neoisopulegol (162b) in 45% yield indicating that it behaves as large catalyst that favors the boat transition state leading to 162b as discussed above (see Scheme 22).…”
Section: Scheme 24mentioning
confidence: 99%
“…1 Me 2 AlCl at À 72 1C. 140 However, aldehyde 224 affords ene adduct 225 in 68% yield with 1 equivalent of Me 2 AlCl at À 72 1C, but not with SnCl 4 . 140 Sarkar reported that the ene reactions of 220 and 222 catalyzed by 5 mol% Sm(III) generated in situ from SmI 2 in CH 2 Cl 2 gives the trans cyclopentanols 226 and 227, respectively rather than the cis cyclopentanols 223 and 225 obtained with Me 2 AlCl or SnCl 4 .…”
Section: Scheme 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Although tin(IV) chloride and dimethylaluminum chloride were considered superior for the cyclization process, titanium(IV) chloride gave mainly chlorhydrins (157) (Scheme 33) [52]. Me 2 AlCl, Et 2 AlCl, EtAlCl 2 , SnCl 4 , TiCl 4 ) were studied in the cyclization of olefinic aldehydes (such as 155) by an internal Prins and/or ene mechanism to afford five-membered rings giving a mixture of products 156-158.…”
Section: Prins Cyclizations 31 Five Membered Rings Formationmentioning
confidence: 99%
“…Several attempts to achieve this transformation by ene reaction [35] or thiazolium-catalysed Stetter reaction [36] in order to maintain the unsaturation on the six-membered ring were unsuccessful. Securing the synthesis of bis-enone 102, it was now possible to attempt the final key step of cyclisation to form the seven-membered ring.…”
Section: Synthetic Strategies Directed Toward the Construction Of Thementioning
confidence: 99%